2022
DOI: 10.1039/d1cp05730h
|View full text |Cite
|
Sign up to set email alerts
|

Generation of multiple triplet states in an orthogonal bodipy dimer: a breakthrough spectroscopic and theoretical approach

Abstract: Generation of triplet states in assemblies of organic chromophores is extremely appealing for their potential use in optoelectronic applications. In this work, we investigate the intricacies of triplet state generation...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…S20, ESI†). This dimerization induced ISC has been rationalized in the past for a variety of compounds, 36,37 including in particular bodipy derivatives, 38–40 and already observed and explained by some of us in a previous report on BTI dimers. 41 Here again, TD-DFT calculations revealed that a strong dynamic excitonic coupling between the two TCI subunits in the TCI 2 dimer result in enhanced spin–orbit coupling constant between the excited singlet and lower triplet states (see Fig.…”
Section: Resultssupporting
confidence: 64%
“…S20, ESI†). This dimerization induced ISC has been rationalized in the past for a variety of compounds, 36,37 including in particular bodipy derivatives, 38–40 and already observed and explained by some of us in a previous report on BTI dimers. 41 Here again, TD-DFT calculations revealed that a strong dynamic excitonic coupling between the two TCI subunits in the TCI 2 dimer result in enhanced spin–orbit coupling constant between the excited singlet and lower triplet states (see Fig.…”
Section: Resultssupporting
confidence: 64%
“…On the basis of the T 1 energy level computed at ca. 1.75 eV for F -BODIPY PM567 and other related dyes ( O -BODIPYs), 15 the long-wavelength band recorded at delay times beyond 200 μs (see Fig. 3) can be reliably assigned to the phosphorescence emission.…”
mentioning
confidence: 87%
“…In this regard, Density Functional Theory (DFT) calculations performed for both non-substituted and similarly functionalized BODIPYs denoted S 1 and T 2 as nearly isoenergetic excited states sustaining rISC to S 1 as competing decay channel. 15…”
mentioning
confidence: 99%
“…In this context, long-lived emissions from commercially available monochromophoric BODIPYs have not been considered due to their assumed lack of effective ISC [ 25 , 26 , 27 ]. Nonetheless, the versatility and performance of laser radiation systems, coupled with high-gain detection equipment, allowed us to record such unexpected long-lived RTP and TADF from aerated solutions of commercial BODIPYs ( Scheme 1 ) [ 28 ]. Such unnoticed phenomenon spans the “well-known” photophysics of one of the most studied dye families so far, allowing for a well-grounded comparison with quantum mechanical methods in predicting the electronic nature of their low-lying excited states.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted using theoretical simulations of the electronically-excited-state properties of BODIPYs [ 28 , 29 , 30 , 31 , 32 , 33 , 34 ], most of them focused on the quantification of the S 1 /S 0 and T 1 /S 1 energy gaps, which is critical to understanding their photophysical behavior upon excitation. However, to the best of our knowledge, none of the conclusions were supported by an accurate correlation with the experimental measurements of prompt and delayed emissions.…”
Section: Introductionmentioning
confidence: 99%